Nomes de domínio - Figueiredo, Apoliana Rodrigues (2020)
The domain name has not only the function of identifying and locating an Internet address, but it is also a distinctive sign, as well as the brand, business name, and establishment title. This year, 2019, it has been 30 (thirty) years since the Brazilian academic community obtained the top domain for the country code (“.br”), used to identify nations or territories (country or location). Currently, the records under the “.br” reach 4 million, placing it in the seventh position among the country domains. The domain name ownership is assigned to the first applicant that submits the registration application, i.e. the arrival time order rule is applied. However, in certain situations, a domain registration may offend third parties’ rights, especially of third parties that own the property of other distinctive signs that are identical or similar to the registered domain name. This results in conflicts, since each institute has its own rules, generating controversies that cause the judiciary and institutions alternative dispute settlements to decide on the legitimacy and right to ownership. In this regard, the object of this research is to study the domain name and the conflicts with the other distinctive signs used mainly in the exercise of business activity, which are not uncommonly confused. The method chosen for this research was qualitative and the research type is bibliographic